Strategies of Music Learning for Children With Special Needs in Kindergarten - Nuryanto, Aliffiya Rizqi; Santoso, Alfine Salsabila Adi (Universitas Negeri Semarang, 2023)
Hj. Isriati Baiturrahman 2 Semarang kindergarten, which is included in the category of public schools, has differences from other public schools, namely there are children with special needs. This study aims to determine the learning process and strategies used in Hj. Israti Baiturahman 2 Semarang Kindergarten. This research uses qualitative research methods, as well as various theories for qualitative research. The result of this study was that during the music learning process, the teachers introduced and listened to several types of songs, such as regional music, to see the children’s responses. And the music learning strategy implemented at TK Hj. Isriati Baiturrahman 2 Semarang is carried out with the process of seeing, imitating, and finding. The strategy is to know the condition of children, especially children with special needs, because of each child's emotional differences. The imitation strategies that teachers use greatly help children in learning comprehension. Learning strategies make teachers more creative in learning in the classroom.